DNA Extraction Method Plays a Significant Role When Defining Bacterial Community Composition in the Marine Invertebrate Echinometra mathaei - Ketchum, Remi N.; Smith, Edward G.; Vaughan, Grace O.; Phippen, Britney L.; McParland, Dain; Al-Mansoori, Noura; Carrier, Tyler J.; Burt, John A.; Reitzel, Adam M. (Frontiers in Marine Science, 2018)
The microbial assemblages of marine organisms play fundamental biological roles in their eukaryotic hosts. Studies aimed at characterizing this diversity have increased over the last decade and with the availability of high-throughput sequencing, we are now able to characterize bacteria that were nonculturable and, therefore, went undetected. With the number of marine microbiome studies growing rapidly, it is increasingly important to develop a set of ‘best practices’ in order to accurately represent the bacterial communities present, and correct for biases. To address this, we sampled the gut communities of the pan-tropical echinoid Echinometra mathaei from two environmentally distinct populations along the Arabian Peninsula. We used three common DNA extraction procedures and compared inferred bacterial diversity from each method through 16S ribosomal RNA (rRNA) gene amplicon sequencing. Our results show that the addition of a bead-beating and lysozyme step more effectively capture traditionally difficult to lyse taxa, such as gram-positive bacteria. Further, DNA extraction method plays an important role in estimates of Shannon diversity, with diversity indices significantly higher in both sites when a lysozyme and bead beating step was used. Finally, we conducted a literature synthesis to highlight the current diversity of approaches used to characterize the microbiome of marine invertebrates and find that the inclusion of a lysozyme treatment is uncommon (2% of surveyed studies), despite the importance of this step in recovery of rare OTUs as shown in our study.